2013
DOI: 10.1038/mt.2013.169
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroprotection and Efficient Regulation of GDNF Using Destabilizing Domains in a Rodent Model of Parkinson’s Disease

Abstract: Glial cell line-derived neurotrophic factor (GDNF) has great potential to treat Parkinson's disease (PD). However, constitutive expression of GDNF can over time lead to side effects. Therefore, it would be useful to regulate GDNF expression. Recently, a new gene inducible system using destabilizing domains (DD) from E. coli dihydrofolate reductase (DHFR) has been developed and characterized. The advantage of this novel DD is that it is regulated by trimethoprim (TMP), a well-characterized drug that crosses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 41 publications
3
81
0
Order By: Relevance
“…The TMP-protein regulation approach does not suffer from these weaknesses. Thus far, studies using TMP regulation in the rodent brain have shown that there are no immunogenic properties associated with the destabilization domain (32). Furthermore, this system has the ability to be finely tuned for tight control of transgene expression by adjusting TMP dosing and expression can be reversed if needed, addressing a major barrier in the development of neuroprotective gene therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TMP-protein regulation approach does not suffer from these weaknesses. Thus far, studies using TMP regulation in the rodent brain have shown that there are no immunogenic properties associated with the destabilization domain (32). Furthermore, this system has the ability to be finely tuned for tight control of transgene expression by adjusting TMP dosing and expression can be reversed if needed, addressing a major barrier in the development of neuroprotective gene therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Combining this approach with a high-expressing promoter, we can reduce the potential silencing effects seen in low-expressing promoters. This makes the system attractive for use in the central nervous system (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, with the use of DD-ecDHFR/TMP, Quintino and collaborators were able to control the level of glial cells-derived neurotrophic factor (GDNF), a protein that exerts neurotrophic and neuroprotective effects on dopamine neurons, in a rodent model of Parkinson's disease (Quintino et al, 2013) confirming the great therapeutic potential of GDNF against Parkinson's disease.…”
Section: Right To Assemblementioning
confidence: 95%
“…In all these studies, the inducer doxycycline was applied for many days or even weeks over the drinking water, it is thus unknown if shortterm doxycycline applications would result in similar effects. In an alternative system depending on stabilization of GDNF fusion proteins coupled to destabilizing domains of E.coli dihydrofolate reductase (DHFR), expressed from a LV vector, striatal GDNF levels of about 125 pg/mg tissue were achieved in the trimethoprim-activated ON-state, while background was low at about 13 pg/mg tissue 33 . In yet another approach, a rapamycinregulated AAV vector expressed GDNF up to 450 pg/mg tissue, without any non-induced background, although by exploiting clinically not acceptable dosages of rapamycin 7 .…”
Section: Comparison Of Background Expression and Induction Efficacy Wmentioning
confidence: 99%